PENGARUH PERLAKUAN PANAS PADA PEMBENTUKAN PELAT BERALUR PANEL KENDARAAN TERHADAP PENINGKATAN FREKUENSI ALAMIAH DIUKUR PADA KONDISI BATAS JEPIT-JEPIT - Sukanto Sukanto; Erwanto Erwanto (ROTOR, 2016)
Vehicle Comfortability in a minibus is highly influenced by the noise level and the mechanical vibration on the cabin. Sound and vibration can come from the engine excitation, the pressure difference in both inside and outside of the cabin, the road roughness and the primary vehicle’s structure. The ground, wall and floor of the cabin in a vehicle are the most influenced parts in the role of transmitting sounds and vibrations. These can be reduced by means of increasing the cabin’s stiffness. Sheet metal is mainly used as the cabin’s material. Its stiffness can also be increased by means of thickening, grooving and embossing the plate. The aims of this experimental work are to increase both the natural frequency and the stiffness of the plate by means of forming and grooving in the cabin’s plate. The material used in this paper is mild steel plate 0,8 mm from galvanized steel that is generally used in manufacturing of the minibus vehicle (ASTM A 29 coated with zinc and aluminum). The research method is derived as follows: determining the panel dimension, calculating the number of the groove, designing both the heating temperature and the cooling media, grooving process, measuring and analyzing the natural frequency and the stiffness. The length and the width of the panel dimension are determined by 550 mm and 550 mm, respectively. Trapezium cross-section is used as groove’s design. The results show that the natural frequency and the stiffness are linearly influenced by residual stress. The highest frequency, reached at 258,06 Hz, is to be found at 10 groove with temperature of 700 °C and followed by water cooling. In addition, this frequency is increased nine times compared with plain panel without groove in which it has 27,55 Hz. Keywords: natural frequency, vehicle panel, heat treatment, fixed-end, stiffness